A study of outcomes of patients treated at a UK major trauma centre for moderate or severe injuries one to three years after injury - Spreadborough, Stephen; Radford, Kathryn A.; das Nair, Roshan; Brooks, Adam; Duffy, Miriam (SAGE, 2017)
Objective: To assess return to work outcomes of major trauma patients treated at a level 1 UK major trauma centre and evaluate factors associated with improved outcomes. Design: Cross-sectional cohort design. Subjects: Ninety-nine Patients at 1, 2 or 3 years post-discharge from a Major Trauma Centre with an injury severity score above 9, in full time work or education prior to injury, aged 18 to 70 and discharged between April 2012 and June 2015. Main Measures: Self report questionnaire including the Trauma Outcome Profile, the Multiple Sclerosis Neuropsychological Screening questionnaire and questions pertaining to work and education. Results: Of the ninety-nine in full time work pre injury, sixty-five made a complete return to work, fifteen made an incomplete return to work, and nineteen did not return to work, where incomplete return to work was defined as working below 80% of previous working hours. Twenty-five participants scored below the cut-off point on physical disabilities, forty-six below the cut-off point on mental functioning and thirty-eight below the cut-off point on social interaction. Reduced anxiety and higher mental functioning was consistently associated with complete return to work. Conclusions: Sixty-six percent of patients with moderate to severe injuries made a complete return to work. A range of psycho-social, physical and functional health issues were persistent at long term follow up.